Strigolactones: new plant hormones in action - Zwanenburg, Binne; Pospíšil, Tomáš; Ćavar Zeljković, Sanja (Planta, 2016)
The key step in the mode of action of strigolactones is the enzymatic detachment of the D-ring. The thus formed hydroxy butenolide induces conformational changes of the receptor pocket which trigger a cascade of reactions in the signal transduction. Strigolactones (SLs) constitute a new class of plant hormones which are of increasing importance in plant science. For the last 60 years, they have been known as germination stimulants for parasitic plants. Recently, several new bio-properties of SLs have been discovered such as the branching factor for arbuscular mycorrhizal fungi, regulation of plant architecture (inhibition of bud outgrowth and of shoot branching) and the response to abiotic factors, etc. To broaden horizons and encourage new ideas for identifying and synthesising new and structurally simple SLs, this review is focused on molecular aspects of this new class of plant hormones. Special attention has been given to structural features, the mode of action of these phytohormones in various biological actions, the design of SL analogs and their applications.
Keywords: Karrikins; Mycorrhizae; Lactones; regulátory růstu rostlin; Signal transduction; Germination; stereoizomerie; mykorhiza; Plant Growth Regulators; Strigolactones; Strigolactone analogs; Strigolactone mimics; Stereoisomerism; Mode of action; laktony; klíčení